ANALISIS YURIDIS IMPLEMENTASI PENYELESAIAN SENGKETA SERTIFIKAT TANAH TUMPANG TINDIH UNTUK MEWUJUDKAN KEPASTIAN HUKUM (STUDI PENELITIAN DI KANTOR BADAN PERTANAHAN KOTA BATAM) - Jose Natanael Kusnadi Putra; Idham Idham; Titik Aminah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Juridical Analysis of the Implementation of Overlapping Land Certificate Dispute Resolution to Realize Legal Certainty. It has been carried out well according to the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 21 of 2020 concerning Handling and Settlement of Land Cases, Law Number 5 of 1960 concerning Agrarian Principles, the Civil Code (KUHPer) , and inhibiting factors of conflicts of interest over land. The qualification/type of writing for this journal uses normative legal writing, and subsequently integrates it with sociological/empirical legal writing. and to analyze some of the problems in this journal, Aristotle's grand theory is used, the middle theory of Jeremy Bentham, while the applied theory of A.V. Dicey. The results of the analysis are still experiencing several obstacles, both internally and externally. Constraints faced include the absence of a meeting or win-win solution when mediation takes place between the two parties when mediation is held at the Batam City Land Agency.Keywords: Dispute, Overlapping Land, Legal Certainty